THE EFFECT OF GENDER, AGE AND ACADEMIC RANK ON WORK-LIFE BALANCE - Marič, Miha; Žnidaršić, Jasmina (International Journal of Economic Practice and Policy, 2019)
Work-life balance has been a topic of various research where researches has been mostly concerned with the influence of organizational practices and policies on work-family balance. On the other side the relation between demographics and work-life balance, particularly in academics sphere, has not been well investigated. Therefore we test in our research how gender, age and the academic rank affect work-life balance among higher education lecturers. Participants in this study were higher education lecturers from Austria, Croatia, Czech Republic, Germany, Serbia and Slovenia. The results of our research show that with a higher academic rank the work-life balance among higher education lecturers’ increases.  Results show no difference in work-life balance among higher education lecturers based on gender. Potential curvilinearity between age and work-life balance among higher education lecturers was not confirmed due to the lack of statistical significance. The results of this study give better insights into the basic demographics’ effect on work-life balance, particularly among higher education lecturers. Results of this study can be used both for further research and in practice.
Keywords: HRM; higher education lecturers; Work-Life Balance